A Comparison of In Situ Analytical Methods for Trace Element Measurement in Gold Samples from Various South African Gold Deposits. Issue 2 (23rd October 2015) - Gauert, Christoph; Schannor, Mathias; Hecht, Lutz; Radtke, Martin; Reinholz, Uwe
Abstract : Trace element concentrations in gold grains from various geological units in South Africa were measured in situ by field emission‐electron probe microanalysis (FE‐EPMA), laser ablation‐inductively coupled plasma‐mass spectrometry (LA‐ICP‐MS) and synchrotron micro X‐ray fluorescence spectroscopy (SR‐μ‐XRF). This study assesses the accuracy, precision and detection limits of these mostly non‐destructive analytical methods using certified reference materials and discusses their application in natural sample measurement. FE‐EPMA point analyses yielded reproducible and discernible concentrations for Au and trace concentrations of S, Cu, Ti, Hg, Fe and Ni, with detection limits well below the actual concentrations in the gold. LA‐ICP‐MS analyses required larger gold particles (> 60 μm) to avoid contamination during measurement. Elements that measured above detection limits included Ag, Cu, Ti, Fe, Pt, Pd, Mn, Cr, Ni, Sn, Hg, Pb, As and Te, which can be used for geochemical characterisation and gold fingerprinting. Although LA‐ICP‐MS measurements had lower detection limits, precision was lower than FE‐EPMA and SR‐μ‐XRF. The higher variability in absolute values measured by LA‐ICP‐MS, possibly due to micro‐inclusions, had to be critically assessed. Non‐destructive point analyses of gold alloys by SR‐μ‐XRF revealed Ag, Fe, Cu, Ni, Pb, Ti, Sb, U, Cr, Co, As, Y and Zr in the various gold samples. Detection limits were mostly lower than those for elements measured by FE‐EPMA, but higher than those for elements measured by LA‐ICP‐MS. Key Points: Trace element concentrations of in‐situ gold grains from various geological units in South Africa Measured by FE‐EMPA, LA‐ICP‐MS, and SR‐μ‐XRF Assessing the accuracy, precision, and detection limits and discussing their application in natural sample measurement